EDUKASI BISNIS PADA PERUSAHAAN LAUNDRY BU RIZMA UNTUK MENGHADAPI PERSAINGAN BISNIS - Michell Putri Fatrisia; Rini Anggriani; Sofian; Diky Ilham; Widya Febriana (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
Mrs. Rizma is an entrepreneur who has a dream of building a successful laundry company. In 2022, Mrs. Rizma started her company with just a few simple washing machines and dryers. The aim of carrying out this activity is to evaluate performance, identify weaknesses and opportunities, and increase efficiency and effectiveness in operations through educational activities to maximize profits. This activity was carried out using the Asset Based Communities Development (ABCD) approach. Educational activities for Bu Azmi's laundry company consist of service quality education, market understanding education, technology and automation education, and business innovation education. In the final stage of education provided by the service team, the Team explained that apart from washing and drying, laundry can also involve a dry cleaning process. Dry cleaning is used to clean clothes made from materials that are sensitive to water, such as silk or wool, or clothes that have stains that are difficult to remove through the normal washing process. This activity has a positive impact on Bu Rizma's Laundry company. After the research team distributed post tests to training participants, the results showed that there was an increase in business understanding.